Directive, Representative, and Expressive Actions in the Interview Rubric Article in the 2019 Edition of the Tirto.Id Online Newspaper - Khairina, Anggi Miftasha Nuri; Pristiwati, Rahayu (Jurusan Bahasa dan Sastra Indonesia Universitas Negeri Semarang, 2021)
The printed mass media is now experiencing development so that it can be accessed through the network or online with the internet. This can be studied using the language through pragmatics. In pragmatics, speech acts are a very important unit of analysis. The researcher chose the Wawancara rubric of the online news site Tirto.id to study because of the unique concept of writing news which is written based on the results of interviews with resource persons. In addition, the articles written in the Wawancara rubric of the online news site Tirto.id contain the intention of explaining, informing something, reporting, advising, and criticizing what is part of the speech act function. This study aims: (1) to analyze the function of directive, representative, and expressive speech acts contained in the discourse of the Wawancara rubric of the online newspaper Tirto.id, (2) to analyze the effects of the discourse on the Wawancara rubric of the online newspaper Tirto .id, (3) analyzing the directive, representative, and expressive speech acts that dominate the discourse of the Wawancara rubric of the online newspaper Tirto.id. This research uses theoretical and methodological approaches. From the results of this study, it is found that the functions of directive speech acts include advising, suggesting, ordering, pressing, begging, asking, inviting, challenging. Representatives include reporting, stating, mentioning, testifying, confessing, demonstrating and speculating. Expressive includes criticizing, praising, complaining, saying congratulations, saying thanks, and blaming, and apologizing. Possible effects of speech are positive, including knowing information, agreeing, thinking about, being happy, hoping to follow, supporting, believing, relieving, proud, and understanding, as well as negative effects including disappointment, disbelief, anger, displeasure, anxiety, ridicule , alert, doubt, and terrifying. The speech acts that tend to be used in writing articles in the